Listening to local narratives about ukuhlonipha and isihlonipho in South Africa. Understanding respect practices through a decolonial lens - (:unkn) unknown (My University, 2024)
This dissertation aims to (re)establish the concept of “ukuhlonipha” in epistemologies of/from the South. The word “ukuhlonipha”, a verb meaning “to respect” in Xhosa or Zulu, has historically been used in the scientific literature to refer to a set of avoidance practices stereotyped to language and to married women. This thesis takes a historical and decolonial standpoint and aims to draw attention to what local discourses frame as “ukuhlonipha” in the Xhosa-speaking and Zulu-speaking contexts. Drawing on from archives written in Xhosa, Zulu and English, from interviews in urban and rural contexts in today’s Xhosa-speaking society, and from a discourse analysis of a social media platform, this thesis intends to show the diversity of realities associated with “ukuhlonipha” in 20th century and 21st century South Africa. By focusing on local narratives, this thesis illustrates how the invention of a linguistic-only and feminine-only “hlonipha” in the scientific literature has contributed to erase several actors from the context of respect practices. Through local endogenous narratives, the thesis shows that “ukuhlonipha” and “isihlonipho/izihlonipho” refer to a set of respectful behaviours which can be language-related but are not exclusively language-related. Moreover, these respectful behaviours regulate social relationships with regard to kinship and gender roles, as well as age and class. Combining historical and contemporary narratives of “ukuhlonipha”, this thesis takes on decoloniality and attempts to spark a discussion about the ways in which respect practices can be apprehended through and contribute to theories of the Global South.
Keywords: African Research